2012
DOI: 10.1155/2012/821936
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Diabetic Nephropathy by Sulforaphane: Possible Role of Nrf2 Upregulation and Activation

Abstract: The present study was to investigate whether sulforaphane (SFN) can prevent diabetic nephropathy in type 1 diabetic mouse model induced by multiple low-dose streptozotocin. Diabetic and age-matched control mice were given SFN at 0.5 mg/kg body weight daily for 3 months. At the end of 3-month SFN treatment, the diabetic nephropathy, shown by renal inflammation, oxidative damage, fibrosis, and dysfunction, was significantly prevented along with an elevation of renal Nrf2 expression and transcription in diabetes/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 33 publications
3
99
1
Order By: Relevance
“…10 And Nrf2 plays a central role in the protective effect against oxidative and apoptosis damage in DN. 11,12 Hence, it was of interest to investigate the role and the proper time nodes of DJ-1/Nrf2 pathway in the pathogenesis of DN in rats.…”
Section: Introductionmentioning
confidence: 99%
“…10 And Nrf2 plays a central role in the protective effect against oxidative and apoptosis damage in DN. 11,12 Hence, it was of interest to investigate the role and the proper time nodes of DJ-1/Nrf2 pathway in the pathogenesis of DN in rats.…”
Section: Introductionmentioning
confidence: 99%
“…SFN has been shown to have similar effects in diabetic nephropathy. 3 months of SFN treatment attenuated loss of kidney function, fibrosis and TGF-β expression, reduced inflammation and TNFα, and oxidative stress in the kidneys of diabetic mice [47,48] [49].…”
Section: Targeting Keap1-nrf2 Dysregulationmentioning
confidence: 91%
“…Under physiological conditions Kelch-like ECH-associated protein 1 (Keap1) binds to Nrf2 and sequesters it in the cytoplasm. Under basal conditions, Keap1 mediates rapid ubiquitination and subsequent degradation of Nrf2 by the proteasome [7,35,36,38]. Studies have demonstrated the beneicial role of Nrf2 induction in the prevention of DN [37].…”
Section: Strategies To Prevent Diabetic Complications By Activating Nmentioning
confidence: 99%
“…Upregulation of these Nrf2-dependent antioxidants promotes detoxiication and anti-inlammatory function. A growing body of evidence has indicated a critical role for activator-induced Nrf2 upregulation in the prevention of diabetic complications, including DN [36].…”
Section: Strategies To Prevent Diabetic Complications By Activating Nmentioning
confidence: 99%